Character Strengths Lead to Satisfactory Educational Outcomes Through Strength Use: A Longitudinal Analysis - Tang, Xiaoqing; Li, Yumei; Duan, Wenjie; Mu, Wenlong; Cheng, Xinfeng (Frontiers in Psychology, 2019)
Despite the flourishing of positive education, understanding of whether different character strengths have different predictive effects on academic achievement/ well-being and the mechanisms of actions between character strengths is limited. Specifically, this study adopted strength use as a mediator to understand well how character strength (assessed by caring, inquisitiveness, and self-control) is associated with students’ end-of-year academic achievements and well-being. Survey data from 349 adolescents from three different schools showed that three factors of character strengths have positive correlations with academic achievements and well-being. Regression models indicated that inquisitiveness and self-control predicted academic achievements, while caring, inquisitiveness, and self-control predicted well-being, with the foremost as the strongest predictor. Mediation analyses indicated that (1) strengths use fully mediated the relationship between inquisitiveness, self-control, and academic achievements/well-being, while (2) caring had a direct effect on well-being. These findings provided possible explanations on how character strengths could affect students’ academic achievements or well-being and theoretical and empirical evidence for practices that aim to enhance students’ academic achievements and positive developments via interventions based on character strengths.